2018
DOI: 10.20473/ijtid.v7i3.7323
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis and Other Intestinal Parasites Infections in Elementary School Children in Dukuh Village, Karangasem District, Bali

Abstract: Blastocystis spp. is the most common enteric parasitic infection found in several community surveys from developing countries. Blastocystis infections may cause gastrointestinal symptoms, but also cause extraintestinal symptoms such as urticaria and joint pain. Blastocystis infection can also be asymptomatic or a carrier. However, the prevalence of Blastocystis infection in children has not yet been fully investigated in Indonesia, particularly in Bali Province. This study aimed to determine the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
2
10
0
6
Order By: Relevance
“…10 Village children in Bali often spend their time playing with the soil and this causes them to be easily infected by bacteria or parasites. [11][12][13][14] The incidence of STH infection in children has brought the attention of the government. The Indonesian government program currently wants to reduce the incidence of helminthiasis in children, both through counseling and deworming for six months on a regular basis, targeting primary school children in remote villages.…”
Section: Resultsmentioning
confidence: 99%
“…10 Village children in Bali often spend their time playing with the soil and this causes them to be easily infected by bacteria or parasites. [11][12][13][14] The incidence of STH infection in children has brought the attention of the government. The Indonesian government program currently wants to reduce the incidence of helminthiasis in children, both through counseling and deworming for six months on a regular basis, targeting primary school children in remote villages.…”
Section: Resultsmentioning
confidence: 99%
“…Kejadian murid PAUD yang positif Giardiasis yaitu sebanyak 5 anak (8,2% (Diarthini et al, 2018). Hasil penelitian Darlan et al pada anak sekolah di Medan diperoleh prevalensi sebesar 4,5% (Darlan et al, 2018).…”
Section: Hasilunclassified
“…While, Mahmood and Khudher (2016) reported a lower rate in Samarra city, which were 3.78% coexistent of B. hominis with E. histolytica and 2.27% with G. lamblia. Furthermore, in several other studies also variable coexistent rates of B. hominis with E. histolytica and G. lamblia were reported, as that carried out by Diarthini et al( 2018) in Dukuh village, Karangasem regency-Bali-Indonesia, they observed that 33.3% of total samples have co-infection with both Blastocystis spp. and Giardia lamblia, while ; in Zanzibar, Tanzania mentioned that two parasitic infection (Blastocystis spp.…”
Section: Discussionmentioning
confidence: 79%